1982
DOI: 10.1029/jb087ib12p10102
|View full text |Cite
|
Sign up to set email alerts
|

Shock‐induced color changes in nontronite: Implications for the Martian fines

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
3
15
1
Order By: Relevance
“…Huck et al, 1977) and the mineralogical causes of the color are currently in dispute (e.g. Smith, 1979, p. 50-52, for early literature;Weldon et al, 1982;Moskowitz and Hargraves, 1981;McCord et al, 1982;Singer, 1982;Sherman et al, 1982). Perhaps brown olivine should be added to nontronite and various iron oxides as possible coloring agents for rocks on Mars.…”
Section: Discussionmentioning
confidence: 99%
“…Huck et al, 1977) and the mineralogical causes of the color are currently in dispute (e.g. Smith, 1979, p. 50-52, for early literature;Weldon et al, 1982;Moskowitz and Hargraves, 1981;McCord et al, 1982;Singer, 1982;Sherman et al, 1982). Perhaps brown olivine should be added to nontronite and various iron oxides as possible coloring agents for rocks on Mars.…”
Section: Discussionmentioning
confidence: 99%
“…The Weldon et al (1982) study, as well as further experiments and characterization by Boslough et a1 (1986), showed that Riverside non tronite that has been shocked or thermally altered achieves colors that span those found on Mars and contains as much ferromagnetic material as the Martian fines do. These studies concluded on that basis that nontronite cannot be excluded as a major constituent of the Martian soil because of known chemical, mineralogical, spectroscopic, or physical properties.…”
Section: Wh Y Is Mars Red?mentioning
confidence: 94%
“…Thus, a substantial fraction of the chemically altered Martian surface material has also been reshocked. Weldon et al (1982) first suggested that the color of the Martian surface materials and their spectral reflectance properties have been modified by their exposure to shock processing. They based their hypothesis on the results of shock experiments on Riverside nontronite, a candidate for the major mineral equivalent in the Martian fines.…”
Section: Wh Y Is Mars Red?mentioning
confidence: 99%
“…This conclusion supports the early findings of Boslough et al [1986], who first observed that color change in shocked nontronite samples differed from that induced by annealing (thermal alteration). It also suggests that the color changes observed in shocked nontronite by Weldon et al [1982] were likely a result of both shock-induced stress and thermal alteration rather than shock-induced thermal alteration alone. It is important to understand the effects of shock and temperature as separate processes because (with the exception of very large impacts) the nonlinear relationship between pressure and temperature in impacts Figure 10.…”
Section: Comparison Of Shock and Thermal Alterationmentioning
confidence: 99%
“…Shock effects have also been invoked to explain the color of the Martian surface. In particular, Weldon et al [] observed that a sample of Riverside nontronite reddened and darkened after experimental impacts between 18 and 30 GPa. Using optical microscopy, X‐ray diffractometry, 57 Fe Mössbauer spectroscopy, and IR spectroscopy, they determined that partial dehydroxylation changed the Fe coordination state and shifted characteristic Fe 3+ /O 2− charge transfer features into the visible wavelength region, producing a redder, darker nontronite sample.…”
Section: Introductionmentioning
confidence: 99%